2016
DOI: 10.4049/jimmunol.1502693
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Langerhans Cells Promote Differentiation of Th17 Cells in a Murine Model of Periodontitis but Are Not Required for Porphyromonas gingivalis–Driven Alveolar Bone Destruction

Abstract: Periodontitis is a chronic oral inflammatory disease affecting one in five individuals that can lead to tooth loss. CD4+ Th cells activated by a microbial biofilm are thought to contribute to the destruction of alveolar bone surrounding teeth by influencing osteoclastogenesis through IL-17A and receptor activator for NF-κB ligand effects. The relative roles of mucosal Ag presentation cells in directing Th cell immune responses against oral pathogens and their contribution to destruction of alveolar bone remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…The murine experimental models were used in 100% of the studies, from which the mouse model was the most frequently used animal model (76.2%) . In the studies using mice, 10 studies used the C57BL/6 strain, four studies used the BALB/c strain, and three studies did not specify the animal strain used . In addition, seven studies used only wild‐type mice, nine studies used both wild‐type and knockout mice, and one study used wild‐type, knockout and the 10BiT mice, corresponding to a IL‐10 reporter animal.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The murine experimental models were used in 100% of the studies, from which the mouse model was the most frequently used animal model (76.2%) . In the studies using mice, 10 studies used the C57BL/6 strain, four studies used the BALB/c strain, and three studies did not specify the animal strain used . In addition, seven studies used only wild‐type mice, nine studies used both wild‐type and knockout mice, and one study used wild‐type, knockout and the 10BiT mice, corresponding to a IL‐10 reporter animal.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies using mice, 10 studies used the C57BL/6 strain, four studies used the BALB/c strain, and three studies did not specify the animal strain used . In addition, seven studies used only wild‐type mice, nine studies used both wild‐type and knockout mice, and one study used wild‐type, knockout and the 10BiT mice, corresponding to a IL‐10 reporter animal. From them, only eight studies reported the number of mice that were analysed (M = 22.6, SD = 8.30, total = 181 mice).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations